1998
DOI: 10.1086/515340
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Kaposi's Sarcoma—Associated Herpesvirus (Human Herpesvirus 8) in Patients with Multiple Myeloma

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) serologic assays were used to detect specific antibodies to KSHV lytic and latent antigens in 27 patients with multiple myeloma, 27 control patients with other cancers, and 50 random blood donors. Antibodies to KSHV recombinant minor capsid antigen orf65 were found in 81% of patients with multiple myeloma, 22% of control patients with other cancers, and 6% of the blood donors. Antibodies to KSHV latent nuclear antigens were found in 52% of patients with multiple m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
0
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 12 publications
3
25
0
2
Order By: Relevance
“…4 While a controversial increased incidence of multiple myeloma and other hematopoietic neoplasms in Classic Kaposi Sarcoma has been extensively reported in the literature, 14,16,18,[21][22][23][24][25][26][27][28][29] the suggested link between HHV-8 and multiple myeloma 30 supports an increase, such as noted in our study, in multiple myeloma in Kaposi Sarcoma patients. An increased incidence of other hematopoietic neoplasms was also observed in our cohort.…”
Section: Discussionsupporting
confidence: 84%
“…4 While a controversial increased incidence of multiple myeloma and other hematopoietic neoplasms in Classic Kaposi Sarcoma has been extensively reported in the literature, 14,16,18,[21][22][23][24][25][26][27][28][29] the suggested link between HHV-8 and multiple myeloma 30 supports an increase, such as noted in our study, in multiple myeloma in Kaposi Sarcoma patients. An increased incidence of other hematopoietic neoplasms was also observed in our cohort.…”
Section: Discussionsupporting
confidence: 84%
“…This conclusion is in line with several serological studies largely performed on different MM populations (Cottoni and Uccini, 1997;Mackenzie et al, 1997;Marcelin et al, 1997;Masood et al, 1997;Whitby et al, 1997;Olsen et al, 1998). The single study that found HHV8 antibodies to be common among MM patients (Gao et al, 1998) used a sensitive immunoblotting method for detection of antibodies against the recombinant minor capsid antigen and latent nuclear antigen of HHV8. The present study did not use immunoblotting for measuring HHV8 antibodies, because our previous prospective study of MM did include immunoblotting against the viral antigens ORF65, ORF73 and ORFK8.1A, but found no association (Tedeschi et al, 2001a).…”
Section: Discussionsupporting
confidence: 71%
“…Several studies found that HHV8 antibodies did not associate with MM (MacKenzie et al, 1997;Masood et al, 1997;Parravicini et al, 1997;Bouscary et al, 1998;Perna et al, 1998;Santarelli et al, 1998;Ablashi et al, 2000), although one study found an association (Gao et al, 1998). However, the large amounts of myeloma proteins in MM patients' sera may induce systematic measurement biases in serological assays.…”
mentioning
confidence: 99%
“…Episome persistence is achieved through direct binding of LANA to the TR and by hooking up the LANA and episomal complex to the host chromatin with the help of cellular proteins (6,35,43,53,59). The number of viral episomal copies ranges from 20 to 150 per cell, and interestingly, the copy number per cell is maintained in tumors as well as in cultured cells after multiple passages (22). This led us to determine the nature of KSHV genome replication.…”
Section: Discussionmentioning
confidence: 99%